Pemanfaatan Dimensi Siber Media dalam Membentuk Citra Keagamaan Selebriti Qari’ di TikTok - Kadri, Wahab; Achmad Fachruddin; Marini (UIN Antasari Banjarmasin, 2024)
This article explores how social media, particularly TikTok, shapes the religious image of Qari' celebrities. It aims to elucidate the process of producing Al-Quran recitations by micro-celebrity ustaz on social media, understand the content and meaning of these recitations, investigate user interactions and responses, and explore the motives behind sharing these recitations. The study uses qualitative methods, focusing on TikTok accounts @ustadzdaeng and @niichaan15. Findings indicate that Al-Quran recitations on social media create immersive experiences for followers and extend the reach of religious messages. The motives for producing these recitations include digital da'wah, promoting religious values, and building a positive image. This article provides insights into the production and impact of Al-Quran recitations by celebrity reciters on social media, highlighting the role of social media in shaping positive religious portrayals.